PERSEPSI ANAK ASUH TERHADAP PENGASUH DI PANTI ASUHAN AS SHOHWAH KELURAHAN SIMPANG BARU KECAMATAN TAMPAN KOTA PEKANBARU - Yogi Halizardi; Wilson Wilson; Daeng Ayub Natuna (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Perception is as a vision or response in the power of understanding or responding. The purpose of this study was to determine the perception of foster children towards caregivers in the As Shohwah Orphanage, Simpang Baru Village, Tampan District, Pekanbaru City. This study consisted of 1 variable, consisting of 4 indicators. The population in this study were 60 Foster Children. This study uses descriptive research with a quantitative approach. The instrument used in this study was a questionnaire containing 66 items of statements to foster children in the orphanage. Data processing techniques in this study by verifying data, grouping items based on indicators, making preparation tables for raw scores, tabulating by making a list of frequency distributions based on indicators and using percentages. Then a descriptive analysis was conducted. From the results of the study, it is proven by the recapitulation presentation that the average percentage is 39.36%, with the percentage of indicators thinking 44.53%, with the percentage of indicators feeling 40.93%, with the percentage of social indicators 42.33%, with the percentage of physical indicators 29.53% classified as poor interpretation. Therefore, it can be stated that some of the Foster Children have different perceptions of caregivers at the Shohwah Orphanage, Simpang Baru Village, Tampan District, Pekanbaru City. Keywords: Perception, Foster Children, Caregivers.